Ultra-small iron carbide nano-particles as well as preparation method and application thereof

By preparing ultra-small iron carbide nanoparticles with a particle size of less than 10 nm, the limitations of existing iron carbide nanoparticles in the fields of T1-MRI and nanozymes have been overcome, achieving multi-enzyme activity and high-efficiency T1 imaging performance, thus expanding its application in the biomedical field.

CN121342028APending Publication Date: 2026-01-16ZHEJIANG UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511528712.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-24
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

The application of existing iron carbide nanoparticles in T1-MRI imaging and nanozymes has limitations. Their magnetic properties are mainly used for T2 imaging, and their enzyme activity is singular and limited in efficiency. They are difficult to efficiently regulate reactive oxygen species in complex physiological environments, which limits their application in chemokinetics and high signal-to-noise ratio imaging.

Method used

Using mesoporous materials as templates, ultra-small iron carbide nanoparticles with a particle size of less than 10 nm were prepared by using organic and inorganic iron sources through hydrothermal reaction, atmospheric calcination and etching. Various surface modifiers were combined to enhance their multi-enzyme activity and T1-MRI performance.

Benefits of technology

The prepared ultrasmall iron carbide nanoparticles possess a variety of nanozyme activities and excellent T1-MRI performance, enabling stable catalysis in complex environments and real-time monitoring of the catalytic process, thus expanding their application potential in the biomedical field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses an ultra-small iron carbide nano-particle and a preparation method and application thereof, the particle size of the ultra-small iron carbide nano-particle is smaller than 10 nm, and the phase composition of the ultra-small iron carbide nano-particle comprises Fe3C, Fe5C2, Fe2C and the like; according to the preparation method, mesoporous silica is taken as a template, organic and inorganic double iron sources are adopted, and the iron carbide nanoparticles which are small in size and uniform in particle size distribution and can be stably dispersed in water for more than 2 months are prepared through the steps of hydrothermal reaction, high-temperature calcination, etching and the like; the ultra-small iron carbide nano-particles obtained by the invention have good activity of various nano-enzymes due to the brand-new image structure and ultra-small size of the nano-particles, and have good T1-magnetic resonance imaging performance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of magnetic nanomaterials, and relates to a novel ultra-small iron carbide nanoparticle with multiple enzyme activities and enhanced T1-magnetic resonance imaging (MRI) performance as well as a preparation method and application thereof. BACKGROUND

[0002] The iron carbide nanoparticle has excellent magnetism, mechanics and catalytic performance and good biocompatibility, and thus has broad application potential in multiple fields such as biological medicine, electronics and chemical industry. As a typical magnetic nanomaterial, the theoretical and application researches thereof have attracted much attention in recent decades. The discovery of the carbon-coated iron carbide structure endows it with more functions: the magnetic iron carbide core can provide excellent magnetic performance and can be applied to T2-magnetic resonance imaging and magnetic control drug delivery; the outer carbon shell can effectively prevent the oxidation and leakage of the core, and can couple drugs or specifically recognize antigens, and at the same time has the fluorescence characteristics of carbon quantum dots, thereby expanding the application prospect of the iron carbide nanoparticle in the biomedical field. Since 2012, when an advanced synthesis scheme was proposed, the related researches have developed rapidly. Compared with iron or iron oxide nanoparticles, the iron carbide nanoparticle has significant advantages, including high saturation magnetization (about 140 emu / g), strong corrosion resistance, good stability and excellent catalytic activity, so that it plays an important role in multiple disciplines. As a ferrous intermetallic compound, the high saturation magnetization of the iron carbide nanoparticle endows it with stronger magnetic responsiveness, and it has been explored and applied in magnetic separation, magnetic targeting, T2-magnetic resonance imaging and magnetic hyperthermia and other technologies.

[0003] As a typical magnetic nanomaterial, the application potential of iron carbide nanoparticles in the biomedical field has been preliminarily concerned. However, there are still obvious limitations in existing research and application. In the aspect of magnetic resonance imaging (MRI), the traditional iron carbide nanoparticles are mainly developed as T2 contrast agents for T2-weighted imaging (T2-MRI) due to their magnetic properties, which severely limits their application in T1-weighted imaging (T1-MRI) which requires high signal-to-noise ratio and clear anatomical structure. In the field of nanozyme, although it is known that iron carbide materials have certain peroxidase-like (POD) activity, their catalytic species are relatively single, and the enzyme activity level is limited, making it difficult to achieve efficient reactive oxygen species (ROS) regulation in complex physiological environments, which restricts its efficiency in chemical kinetic therapy and other scenarios. Therefore, developing a new type of iron carbide nanomaterial with excellent T1-MRI contrast performance and high-efficiency, broad-spectrum enzyme-like catalytic activity has become a clear and urgent technical problem in this field. The ultra-small iron carbide nanomaterial not only has efficient peroxidase-like (POD) activity, but also can catalyze hydrogen peroxide (H2O2) to produce highly reactive hydroxyl radicals (·OH), and has superoxide dismutase-like (SOD) and catalase-like (CAT) activity. This unique multi-enzyme activity coordination system enables it to intelligently regulate the conversion path and steady-state concentration of hydrogen peroxide and other reactive oxygen species (ROS) according to different reaction microenvironments, exhibiting strong catalytic adaptability and controllability. In addition, its ultra-small size (2-3 nm) and moderate paramagnetism make it also perform excellently as a high-performance T1-weighted magnetic resonance imaging (MRI) contrast agent, providing a unique technical means for real-time monitoring of the catalytic process. The synergistic effect of carbon and iron further ensures the structural and catalytic stability of the material in complex chemical environments. Based on the above characteristics, the material provides an ideal core for constructing an intelligent nano-platform based on catalytic chemistry, and can further expand its applications in environmental catalysis, biosensing, and disease diagnosis and treatment by combining with other functional components. SUMMARY

[0004] The application provides an ultra-small iron carbide nanoparticle, a preparation method and application thereof. The prepared iron carbide nanoparticle has a small size (<10 nm), a uniform particle size distribution, excellent multiple enzyme-like activities and T1-magnetic resonance imaging (T1-MRI) performance, and has important significance and broad application prospects in the field of nanozyme.

[0005] In order to solve the above technical problems, the technical scheme adopted by the application is: In a first aspect, the application provides a new multifunctional ultra-small iron carbide nanoparticle, which has a particle size of less than 10 nm and a phase composition including Fe3C, Fe5C2, Fe2C and the like.

[0006] A method for preparing ultrasmall iron carbide nanoparticles using a confined template method involves using mesoporous materials as templates and a dual iron source (organic and inorganic) through multiple steps including hydrothermal reaction, atmospheric calcination, and etching. Specifically: (1) Preparation of mesoporous templates (taking mesoporous silica as an example): Hexadecyltrimethylammonium bromide (CTAB) and triethanolamine (TEA) were dissolved in deionized water, kept warm in a water bath, and tetraethyl silicate (TEOS) was slowly added dropwise. The mixture was kept warm in a water bath at 80°C for 2 hours. After washing, separation, drying, and grinding, the sample was calcined in a tube furnace at 600°C for 8 hours to obtain mesoporous silica powder.

[0007] (2) Dissolve the organic iron source in an organic solvent (solution A) and the inorganic iron source in deionized water (solution B). Mix solutions A and B and add the mesoporous silica prepared in step (1). Stir and then place in a reaction vessel for hydrothermal reaction. The sample is washed, dried, ground, etc., to obtain intermediate product 1. The organic iron sources include ferrous gluconate, sodium iron tetraacetate oxalate, sodium iron diethylenetriaminepentaacetate, ferric citrate, ferric acetylacetone, ferrocene, ferric carbonyl, ferrous fumarate, ferric citrate, and other organic iron compounds with more than 3 carbon atoms; the inorganic iron sources are water-soluble iron salts that can dissociate iron ions in aqueous solution, such as ferric chloride hexahydrate, ferric nitrate pentahydrate, and ferric sulfate.

[0008] (3) Intermediate product 1 was calcined in hydrogen atmosphere and carbon monoxide atmosphere to obtain intermediate product 2.

[0009] (4) Intermediate product 2 is etched in an alkaline etchant containing a surface modifier for a certain period of time, and after washing, separation and drying, ultra-small iron carbide nanoparticles are obtained. The surface modifier is a water-soluble organic molecule containing multiple coordination functional groups (such as carboxyl, mercapto, and phenolic hydroxyl groups), such as citric acid, dopamine, dimercaptosuccinic acid, protocatechuic acid, catechin, trisodium citrate, and polyethylene glycol.

[0010] Preferably, the pore size of the mesoporous silica in step (1) is 30-70 nm.

[0011] Preferably, the organic dispersion solvent used in step (2) is a low molecular weight alcohol solvent such as ethanol, methanol, or ethylene glycol; the mass ratio of organic iron source to inorganic iron source is 1:1-1:6; the mass ratio of inorganic iron source to mesoporous silica is 1:1-2:1; the hydrothermal reaction temperature is 160-220℃; and the reaction time is 4-36h.

[0012] Preferably, in step (3), the hydrogen content in the hydrogen atmosphere calcination is controlled at 5%-35%, the calcination temperature is 500-1500℃, and the calcination time is 2-8h. In the carbon monoxide atmosphere calcination, the carbon monoxide content is controlled at 10%-40%, the calcination temperature is 500-1500℃, and the calcination time is 2-10h.

[0013] Preferably, the pH value of the etchant in step (4) is controlled at 10-14, the concentration of the surface modifier is controlled at 0.05 mol / L or higher, and the etching time is controlled at 12-36 h.

[0014] Thirdly, the present invention provides an application of the ultrasmall iron carbide nanoparticles prepared by the above method in various nanozymes and T1-magnetic resonance imaging (MRI) performance.

[0015] By adopting the above-described technical solution, the present invention achieves the following technological advancements and beneficial effects compared to existing technologies: (1) This invention uses mesoporous silica as a template and employs organic and inorganic dual iron sources. Through hydrothermal reaction, high-temperature calcination, etching and other steps, iron carbide nanoparticles with small size (<10nm) and uniform particle size distribution are prepared and can remain stably dispersed in water for more than 2 months.

[0016] (2) The ultra-small iron carbide nanoparticles obtained in this invention have good multi-nanozyme activity, which is due to their novel physical structure and ultra-small size, and have good T1-magnetic resonance imaging (MRI) performance. Attached Figure Description

[0017] Figure 1 This is a transmission electron microscope (TEM) image of the mesoporous silica particles in Example 1; Figure 2 This is a transmission electron microscope (TEM) image of intermediate product 1 in Example 4; Figure 3 This is a transmission electron microscope (TEM) image of intermediate product 2 in Example 4; Figure 4 This is the X-ray diffraction (XRD) pattern of intermediate product 2 in Example 4; Figure 5 This is a transmission electron microscope (TEM) image of the ultra-small iron carbide nanoparticles in Example 4; Figure 6 The POD-like enzyme activity of the ultra-small iron carbide nanoparticles in Example 5; Figure 7 This is a comparison of the POD-like enzyme activities of ultra-small iron carbide (Fe3C) nanoparticles, traditional iron tetroxide (Fe3O4) nanoparticles, and ultra-small iron tetroxide (Fe3O4) nanoparticles in Example 6. Figure 8 The SOD-like enzyme activity of the ultra-small iron carbide nanoparticles in Example 7; Figure 9 The CAT enzyme-like activity of the ultra-small iron carbide nanoparticles in Example 8; Figure 10The T1-magnetic resonance imaging (MRI) performance of the ultra-small iron carbide nanoparticles in Example 9; Detailed Implementation

[0018] The present invention will be further described below with reference to specific embodiments. However, the experimental conditions and setting parameters therein should not be regarded as limitations on the basic technical solution of the present invention, and the protection scope of the present invention is not limited to the scope of the embodiments described below. Example

[0019] This embodiment describes a method for preparing mesoporous silica particles, including the following steps: CTAB (0.004 mol) and TEA (0.001 mol) were dissolved in deionized water (100 mL), and the mixture was kept in a water bath at 85°C for 1 hour. TEOS (0.07 mol) was then slowly added dropwise, and the reaction continued for another 4 hours. The product was centrifuged, dried, and ground, then calcined in a tube furnace at 600°C for 8 hours to obtain mesoporous silica particles with a particle size of approximately 50 nm. Figure 1 As shown. Example

[0020] This embodiment describes a method for preparing ultrasmall iron carbide nanoparticles, including the following steps: Ferric acetylacetone (1 mmol) was dissolved in anhydrous ethanol (10 mL), and ferric chloride hexahydrate (5.9 mmol) was dissolved in deionized water (10 mL). After mixing the two solutions thoroughly, mesoporous silica particles (0.3 g) were added, and the mixture was hydrothermally reacted at 160 °C for 6 h. After washing, drying, and grinding, intermediate product 1 was obtained.

[0021] Intermediate product 1 was placed in a tube furnace and calcined at 600°C for 2 hours in a hydrogen / nitrogen mixed atmosphere with a volume ratio of 5:95. Subsequently, the atmosphere was adjusted, and a carbon monoxide / argon mixed atmosphere with a volume ratio of 10:90 was introduced into the tube furnace, and calcined at 550°C for 2 hours. Intermediate product 2 was obtained.

[0022] Sodium hydroxide (0.125 mol) and protocatechuic acid (0.003 mol) were dissolved in deionized water (50 mL) to prepare an etching solution. 10-20 mL of the etching solution was taken and intermediate product 2 was added. After shaking and etching for 24 h, the solution was dialyzed for three days to obtain ultra-small iron carbide nanoparticles with a size of about 2-3 nm. Example

[0023] This embodiment describes a method for preparing ultrasmall iron carbide nanoparticles, including the following steps: Sodium iron oxalate tetraacetate (1 mmol) was dissolved in anhydrous ethanol (10 mL), and ferric nitrate (4 mmol) was dissolved in deionized water (10 mL). After mixing the two solutions thoroughly, mesoporous silica particles (0.26 g) were added, and the mixture was hydrothermally reacted at 220 °C for 36 h. After washing, drying, and grinding, intermediate product 1 was obtained.

[0024] Intermediate product 1 was placed in a tube furnace and calcined at 1200°C for 8 hours in a hydrogen / nitrogen mixed atmosphere with a volume ratio of 35:65. Subsequently, the atmosphere was adjusted, and a carbon monoxide / argon mixed atmosphere with a volume ratio of 40:60 was introduced into the tube furnace, and calcined at 1200°C for 10 hours. Intermediate product 2 was obtained.

[0025] Sodium hydroxide (0.125 mol) and protocatechuic acid (0.003 mol) were dissolved in deionized water (50 mL) to prepare an etching solution. 10-20 mL of the etching solution was taken and intermediate product 2 was added. After shaking and etching for 24 h, the solution was dialyzed for three days to obtain ultra-small iron carbide nanoparticles with a size of about 2-3 nm. Example

[0026] This embodiment describes a method for preparing ultrasmall iron carbide nanoparticles, including the following steps: Ferric acetylacetone (0.5 mmol) was dissolved in anhydrous ethanol (10 mL), and ferric nitrate (1 mmol) was dissolved in deionized water (10 mL). After thorough mixing, mesoporous silica particles (0.09 g) were added, and the mixture was hydrothermally reacted at 180 °C for 24 h. The sample was washed, dried, and ground to obtain intermediate product 1, as shown... Figure 2 As shown.

[0027] Intermediate product 1 was placed in a tube furnace and calcined at 650°C for 5 h in a hydrogen / nitrogen mixed atmosphere with a volume ratio of 15:85. Subsequently, the atmosphere was adjusted, and a carbon monoxide / argon mixed atmosphere with a volume ratio of 20:80 was introduced into the tube furnace, and calcined at 650°C for 6 h. Intermediate product 2 was obtained, and the phase and morphology characterization results of this product are as follows: Figure 3 and Figure 4 As shown.

[0028] Sodium hydroxide (0.125 mol) and protocatechuic acid (0.003 mol) were dissolved in deionized water (50 mL) to prepare an etching solution. 10-20 mL of the etching solution was taken, and intermediate product 2 was added. After shaking and etching for 24 hours, the mixture was dialyzed for three days to obtain ultra-small iron carbide nanoparticles with a size of approximately 2-3 nm. Figure 5 As shown. Example

[0029] This embodiment describes the detection of POD-like enzyme activity in ultra-small iron carbide nanoparticles, including the following steps: The POD-like enzyme activity of ultrasmall iron carbide nanoparticles was detected using 3,3',5,5'-tetramethylbenzidine (TMB) as an indicator. Figure 6 As shown, under weakly acidic conditions, the sample solution turned blue with the addition of ultra-small iron carbide nanoparticles, indicating that the ultra-small iron carbide nanoparticles reacted with TMB. The maximum absorption peak was observed at 652 nm, indicating that the ultra-small iron carbide nanoparticles have POD-like enzyme activity and can effectively catalyze the oxidation of TMB. Example

[0030] This embodiment compares the POD-like enzyme activity of ultra-small iron carbide (Fe3C) nanoparticles with that of traditional iron(III) oxide (Fe3O4) nanoparticles and ultra-small iron(III) oxide (Fe3O4) nanoparticles, and includes the following steps: The specific steps are as follows: Add 50 μL of the corresponding nanoparticle solution (concentration 100 μg / mL), 50 μL of TMB solution (concentration 10 mg / mL), and 4 μL of 30% H2O2 solution to 5 mL of sodium acetate buffer (pH 4.5) to initiate the reaction. Incubate the reaction system at 37℃ for 15 minutes, and then measure the absorbance at 652 nm using a UV-Vis spectrophotometer.

[0031] Experimental results are as follows Figure 7 As shown, the absorbance of the ultrasmall iron carbide (Fe3C) nanoparticle group at 15 minutes of reaction was 1.36±0.02, significantly higher than that of the traditional iron tetroxide (Fe3O4) nanoparticle group (0.12±0.02) and the ultrasmall iron tetroxide (Fe3O4) nanoparticle group (0.46±0.02). This result clearly confirms that, under the same conditions, the ultrasmall iron carbide nanoparticles possess superior POD-like enzyme catalytic activity. Example

[0032] This example demonstrates the detection of SOD-like enzyme activity in ultra-small iron carbide nanoparticles, measuring the superoxide radical (·O2) content in sample solutions of different concentrations. - The determination of the scavenging ability of ) includes the following steps: Prepare Tris solution (0.1 mol / L), HCl solution (0.1 mol / L), and pyrogallol solution (60 mmol / L, dissolved in 1 mmol / L hydrochloric acid). Tris-HCl buffer: Take 40 mL of 0.1 mol / L Tris solution, add 0.1 mol / L HCl solution and 15.2 mg Na₂EDTA, mix well, and dilute to 80 mL, adjusting the pH to 7.4. Then, add 2950 μL of Tris-HCl buffer to a quartz cuvette, followed by 50 μL of pyrogallol solution. Vortex mix immediately and start timing. Use a UV spectrophotometer to read the absorbance at 325 nm every 30 s until 300 s. Then, A₀ = A 300s - A 30s Finally, sample solutions of different concentrations were added to quartz cuvettes, Tris-HCl buffer was added to a total volume of 2950 μL, and then 50 μL of pyrogallol solution was added. The mixture was immediately vortexed, and timing was started. The absorbance was read every 30 seconds at 325 nm using a UV spectrophotometer until 300 seconds, at which point A was determined. 样 = A 300s - A 30s Calculation formula: O2 - Clearance rate = (A0 - A) 样 ) / A0×100%. Based on the formula, calculate the superoxide radicals (·O2) of ultrasmall Fe3C nanoparticles with different concentrations. - ) clearance rate, such as Figure 8 As shown. Example

[0033] This embodiment describes the detection of CAT-like enzyme activity in ultra-small iron carbide nanoparticles, including the following steps: The catalase activity of the samples was detected using a dissolved oxygen meter. Sample concentration variations were observed by taking different volumes (80, 120, 180, 270 μL) of sample dispersion (1 mg / mL). -1 Mix PBS buffer (pH 7.4) to a total volume of 2.5 mL, then add 40 μL of 30% H2O2 solution to start the reaction. The dissolved oxygen concentration in the reaction system was monitored using a dissolved oxygen meter, with dissolved oxygen values ​​recorded every 30 seconds for up to 300 seconds. Figure 9 The graph shows the catalytic generation of H2O2 by ultra-small iron carbide nanoparticles at different concentrations. As the concentration of the material increases, the rate of dissolved oxygen generation increases significantly, which strongly proves that the ultra-small iron carbide nanoparticles possess CAT activity. Example

[0034] This embodiment describes the magnetic resonance imaging (MRI) performance characterization of ultrasmall iron carbide nanoparticles, including the following steps: A gradient concentration solution of Fe3C NPs was prepared (solvent: deionized water, iron atom concentrations: 0.0143, 0.0287, 0.0430, 0.0573, 0.0717, 0.1146, 0.1433, 0.1791, 0.2150, 0.2866 mM). Detection was performed using a 3.0 T clinical MRI scanner (Siemens Skyra) at 37°C. 1. Measurement of T1 relaxation time: Sequence: Inversion Recovery (IR-TSE), parameters: TR=5000 ms, TE=12 ms, TI=50–2500 ms (16 points); The T1 value for each concentration was calculated by fitting the formula S = |A - B·exp(-TI / T1)|. T1 relaxation rate (r1) calculation: A linear fit was performed with the reciprocal of concentration on the x-axis and 1 / T1 on the y-axis, and the slope was the r1 value.

[0035] like Figure 10 As shown, the T1 relaxation rate of Fe3C NPs is r1 = 8.72 mM. -1 s -1 This confirms its high T1 contrast enhancement capability; the concentration-dependent curve shows strict linearity, meeting the standards for clinical contrast agents. The ultra-small size (2-3 nm) of Fe3C NPs promotes short-range diffusion of water protons, significantly shortening the T1 relaxation time; the ultra-high r1 value (8.72 mM) further enhances its performance. -1 s -1 Due to its low magnetic properties and surface proton exchange effect, this material can be used as a high-performance T1 contrast agent for precise tumor diagnosis.

[0036] In summary, this invention provides a method for preparing ultrasmall iron carbide nanoparticles using a confined template method. The ultrasmall iron carbide nanoparticles prepared by this method exhibit uniform particle size distribution, high stability, and can be effectively stored for several months. The ultrasmall iron carbide nanoparticles obtained by this invention possess excellent activity for various nanozymes and T1-magnetic resonance imaging (MRI) performance.

Claims

1. An ultra-small iron carbide nanoparticle, characterized by: The super-small carbonized iron nanoparticles have a particle size less than 10 nm, and a phase composition including but not limited to Fe3C, Fe5C2 and Fe2C.

2. A method of preparing ultra-small iron carbide nanoparticles, characterized by: A porous template with a pore size of 30-70 nm is prepared; the super-small carbonized iron nanoparticles are prepared by a hydrothermal reaction-atmosphere calcination-etching process using a mesoporous material as a template and organic and inorganic iron sources.

3. The method for preparing ultra-small iron carbide nanoparticles according to claim 2, characterized in that: The organic iron source is an organic iron-containing compound with more than 3 carbon atoms.

4. The method for preparing ultra-small iron carbide nanoparticles according to claim 2, characterized in that: The inorganic iron source is a water-soluble iron salt that can dissociate iron ions in an aqueous solution.

5. The method for preparing ultra-small iron carbide nanoparticles according to claim 2, characterized in that: The hydrothermal reaction process is as follows: the organic iron source is dissolved in an organic dispersant, the inorganic iron source is dissolved in deionized water, and then the hydrothermal reaction is carried out after sufficient stirring and uniformity, the hydrothermal reaction temperature is 160-220 DEG C, and the reaction time is 4-36 h.

6. The method for preparing ultra-small iron carbide nanoparticles according to claim 2, characterized in that: The atmosphere calcination includes hydrogen atmosphere calcination and carbon monoxide atmosphere calcination.

7. The method for preparing ultrasmall iron carbide nanoparticles according to claim 6, characterized in that: The hydrogen atmosphere calcination has a hydrogen content of 5%-35%, a calcination temperature of 500-1500 DEG C, and a calcination time of 2-8 h; the product after hydrogen calcination is calcined in a carbon monoxide atmosphere, the carbon monoxide content is controlled to be 10%-40%, the calcination temperature is 500-1500 DEG C, and the calcination time is 2-10 h.

8. The method for preparing ultra-small iron carbide nanoparticles according to claim 2, characterized in that: The etching agent in the etching process is composed of an alkaline solution containing a surface modifier; the solution pH value is controlled to be 10-14; the surface modifier is a water-soluble organic molecule containing multiple coordination functional groups, and the concentration of the surface modifier is controlled to be more than 0.05 mol / L.

9. The method for preparing ultra-small iron carbide nanoparticles according to claim 2, characterized in that: The organic dispersant used includes low molecular alcohol solvents; the mass ratio of the organic iron source to the inorganic iron source is 1:1-1:6; and the mass ratio of the inorganic iron source to the mesoporous silica is 1:1-2:

1.

10. The super-small carbonized iron nanoparticles prepared by any one of claims 1 to 9 are used for artificial nanoscale enzymes and T1-magnetic resonance imaging contrast agents.

Citation Information

Cited By

  • In-situ grown iron carbide film electrode and preparation method and application thereof

    CN122532005A